Genome-wide identification, phylogeny, and expression analysis of GRF transcription factors in pineapple (Ananas comosus) - Yi, Wen; Luan, Aiping; Liu, Chaoyang; Wu, Jing; Zhang, Wei; Zhong, Ziqin; Wang, Zhengpeng; Yang, Mingzhe; Chen, Chengjie; He, Yehua (Frontiers in Plant Science, 2023)
Pineapple is the only commercially grown fruit crop in the Bromeliaceae and has significant agricultural, industrial, economic, and ornamental value. GRF (Growth-regulating factor) proteins are one of the important transcription factors that have evolved in seed plants (embryophytes). They contain two conserved domains, QLQ (Gln, Leu, Gln) and WRC (Trp, Arg, Cys) and regulate all aspects of plant growth and stress response, including floral organ development, leaf growth, and hormone responses. The GRF family has been characterized in a number of plant species, but little is known about the family in pineapple and other bromeliads.We identified eight GRF transcription factor genes in pineapple, and phylogenetic analysis placed them into five Subfamilies (I, III, IV, V, VI). Segmental duplication appeared to be the major contributor to expansion of the AcGRF family, and the family has undergone strong purifying selection during evolution. Relative to that of other gene families, the gene structure of the GRF family showed less conservation. Analysis of promoter cis-elements suggested that AcGRF genes are widely involved in plant growth and development. Transcriptome data and qRT-PCR results showed that, with the exception of AcGRF5, the AcGRFs were preferentially expressed in the early stage of floral organ development, and AcGRF2 was strongly expressed in ovules. Additionally, we found that gibberellin treatment significantly induced AcGRF7/8 expression, suggesting that these two members may be involved in the molecular regulatory pathway of gibberellin to promote pineapple fruit expansion.AcGRF proteins appear to play an important role in the regulation of floral organ development and the response to gibberellin. The information reported here provides a foundation for further study of the functions of AcGRF genes and the traits they regulate.